First report of cross-resistance of goosegrass (Eleusine indica) to ACCase inhibitors in Paraná - Freitas, Mateus Luiz de Oliveira; Witter, Ana Paula Werkhausen; Nalin, Daniel; Sanches, Ana Karoline Silva; Oliveira Junior, Rubem Silvério de; Biffe, Denis Fernando; Constantin, Jamil; Granzioli, Lucas (Revista de Ciências Agroveterinárias, 2024)
Goosegrass (Eleusine indica) is a plant that has caused many problems in Brazil, mainly due to the problems associated to chemical control in grain producing areas. The objective of this work was to investigate the eventual cross-resistance to ACCase (acetyl-CoA carboxylase enzyme) inhibitor herbicides in a biotype collected in Paranacity (PR). Herbicides evaluated included fluazifop-p-butyl; quizalofop-p-ethyl, haloxyfop-p-methyl, sethoxydim and clethodim. Dose-response curves were elaborated under greenhouse conditions using completely randomized design trials in a 9x2 factorial scheme with four replicates. The levels of the first factor correspond to the nine doses of each herbicide and the levels of the second factor refer to the susceptible and suspected resistance biotypes. The selected doses corresponded to 0; 1/16; 1/8; 1/4; 1/2; 1; 2; 4; and 8 times the labeled dose for each herbicide and all herbicides were applied at the stage of one tiller. The results indicated that the Paranacity biotype was susceptible to clethodim and quizalofop-p-ethyl, however, it was poorly controlled by fluazifop-p-butyl, haloxyfop-p-methyl and sethoxydim. The resistance factor for these herbicides were determined to be 10.66; 5.64; and 9.8, respectively. The biotype from Paranacity was characterized as resistant to fluazifop-p-butyl, haloxyfop-p-methyl and sethoxydim. constituting the first case of cross-resistance to ACCase inhibitors in the state of Paraná.